Pancasila Democracy and the Implementation of an Open Proportional Electoral System - Puspahani, Ika; Saleh, Moh (Jurnal Mengkaji Indonesia, 2024)
Abstract: This research focuses on the constitution-based election system. Theoretically, there are two general election systems: the district and proportional. Proportional systems aim to reflect the statistical portrait of the population in the representation body, while the district system adheres to the 'one man one vote' principle. The open proportional electoral system, mandated by Constitutional Court Decision No. 22-24/PUU-VI/2008, aims to provide voters with a direct and open choice in selecting legislative candidates. Purpose: This article endeavors to scrutinize the congruence between the implementation of the open proportional electoral system and the essence of Pancasila democracy, the fundamental principle underpinning Indonesia's legal and political framework. Design/Methodology/Approach: This legal inquiry employs a normative approach, analyzing secondary data and legal principles to investigate the implementation of the open proportional electoral system and its compatibility with the tenets of Pancasila democracy. Findings: The open proportional electoral system, as mandated by Constitutional Court Decision No. 22-24/PUU-VI/2008, underscores the active involvement of citizens in the selection of legislative representatives. This system establishes a more direct and accountable linkage between voters and their elected representatives, thereby aligning with the foundational principles of Pancasila democracy. Originality/value: This research underscores the significance of examining the correlation between the proportional electoral system and the essence of Pancasila democracy. It posits a compelling argument in favor of aligning the electoral system with the principles of democratic representation and citizen participation in the Indonesian context.